Modelling and Observation of Exhaust Gas Concentrations for Diesel Engine Control - Blanco-Rodriguez, Dr.-Ing. David (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
The book presents a complete new methodology for the on-board measurements and modeling of gas concentrations in turbocharged diesel engines. It provides the readers with a comprehensive review of the state-of-art in NOx and lambda estimation and describes new important achievements accomplished by the author. These include: the online characterization of lambda and NOx sensors; the development of control-oriented models of lambda and NOx emissions; the design of computationally efficient updating algorithms; and, finally, the application and evaluation of the methods on-board. Because of its technically oriented approach and innovative findings on both control-oriented algorithms and virtual sensing and observation, this book offers a practice-oriented guide for students, researchers and professionals working in the field of control and information engineering.